Parabolic Pulse Generation Using Tapered Microstructured Optical Fibres - Vukovic, Natasha; Broderick, Neil G. R.; Poletti, Francesco (Advances in Nonlinear Optics, 2008)
This paper presents a numerical study of parabolic pulse generation in tapered microstructured optical fibres (MOFs). Based on our results and the algorithms presented, one can determine the linear taper profile (starting and finishing pitch values and taper length) needed to achieve parabolic pulse shaping of an initial Gaussian pulse shape with different widths and powers. We quantify the evolution of the parabolic pulse using the misfit parameter and show that it is possible to reach values significantly better than those obtained by a step index fibre.